L’objet incorporé et la logique des situations - Nicolas Veyrat; Éric Blanco; Pascale Trompette (Revue d'anthropologie des connaissances)
The development of new (micro- and nano-) technologies goes toward a tighter relationship between the artefact and the human body; techniques’ miniaturization, and their enhanced portability, work in favour of wearable devices (sometimes considered as incorporated). Those informational or smart prosthesis blur the original status of artefacts, based on exteriority… This paper intends to question such coupling forms between human beings and their equipment. The exploration of both a secular and common object, namely eyeglasses, enables us to prepare the ground for the analysis of the relationships between incorporation and exteriority, between continuity and discontinuity of artefact’s associations. From various close-ups at historical sociotechnical configurations to a gaze at the contemporary object, we suggest that material and environmental circumstances should be reintroduced in the analysis of subject-object couplings. The corporal object is certainly not exempt from a permanent requestioning of its involvement into several situations, from a continuous attachment to the body to an incorporation to the surrounding sociotechnical network.